New media and its Relationship to Social change - boulsen, nadjat (Journal of Social Sciences and Humanities, 2024)
Human societies have witnessed fundamental transformations that have contributed to change their social structure, in which social change was considered one of the main concepts that contributed to the production of sociological approaches that analyze and interpret its meaning ”as a phenomenon associated with social life”. According to researcher Anthony Giddens, one of the pioneers of socio-media analysis, common transformation occurs in society due to a change in systems, standards, values, and social relationships. and on the other hand he believes that media technology is a means to achieve This social change. This study has used a descriptive and analytic method in order to syudy the problem of social change during the new media ,From this standpoint, we must find answers to the following questions: what is meant by social change ?and what are its patterns and obstacles? How is the new media affected by social change?.